Industrial Patenting Drivers: A Case Study from a Multinational Steel Company - Pérez Villa, Walter (2022)
Intellectual property is a key aspect in the current business environment and one of its main indicators is the request and filing of patents. This study explores the motivation that both researchers and industrial private companies have when it comes to patenting the results of their research. To do this, a case study of one of the largest multinational organizations in the steel sector is analyzed, focusing on the motivations that industrial researchers  and  a  large  manufacturing  organization  have  today  when  filing  their  inventions.In this case, the patents registered over thirty years of this company and its predecessor ones by nearly half a thousand researchers have been analyzed, while semi-structured interviews  were  conducted  with  experts  from  the  company.  Despite  of  being  a  technologically  mature  sector,  it  has  been  found  that  patents  have  a  growing  trend  which, in turn, follows the global inclination in terms of patent applications, which has not stopped growing since 2009 and may have increases in the number of applications of up to 10 % year-on-year.It  has  been  found  that  organizations  use  to  patent  to  protect  not  only  their  finished  products, but also products and processes that are at an early stage of development, thereby preventing their competitors from entering certain lines of work that could lead to future marketable products or innovative manufacturing processes. From their side, industrial researchers consider the patent application as one of the objectives of their career and the patent constitutes itself a recognition of their work.